Microfluidic device for enhancement and analysis of osteoblast differentiation in three-dimensional cell cultures - Michael Killinger; Adéla Kratochvilová; Eva Ingeborg Reihs; Eva Matalová; Karel Klepárník; Mario Rothbauer (Journal of Biological Engineering)
Abstract Three-dimensional (3D) cell cultures are to date the gold standard in biomedical research fields due to their enhanced biological functions compared to conventional two-dimensional (2D) cultures. 3D cell spheroids, as well as organoids, are better suited to replicate tissue functions, which enables their use both as in vitro models for basic research and toxicology, as well as building blocks used in tissue/organ biofabrication approaches. Culturing 3D spheroids from bone-derived cells is an emerging technology for both disease modelling and drug screening applications. Bone tissue models are mainly limited by the implementation of sophisticated devices and procedures that can foster a tissue-specific 3D cell microenvironment along with a dynamic cultivation regime. In this study, we consequently developed, optimized and characterized an advanced perfused microfluidic platform to improve the reliability of 3D bone cell cultivation and to enhance aspects of bone tissue maturation in vitro. Moreover, biomechanical stimulation generated by fluid flow inside the arrayed chamber, was used to mimic a more dynamic cell environment emulating a highly vascularized bone we expected to improve the osteogenic 3D microenvironment in the developed multifunctional spheroid-array platform. The optimized 3D cell culture protocols in our murine bone-on-a-chip spheroid model exhibited increased mineralization and viability compared to static conditions. As a proof-of-concept, we successfully confirmed on the beneficial effects of a dynamic culture environment on osteogenesis and used our platform for analysis of bone-derived spheroids produced from primary human pre-osteoblasts. To conclude, the newly developed system represents a powerful tool for studying human bone patho/physiology in vitro under more relevant and dynamic culture conditions converging the advantages of microfluidic platforms with multi-spheroid array technologies. Graphical Abstract